2019
DOI: 10.1111/jdi.13003
|View full text |Cite
|
Sign up to set email alerts
|

Lower body mass index is not of more benefit for diabetic complications

Abstract: Aims/Introduction To investigate the relationship between different body mass index (BMI) levels and vascular complications in type 2 diabetes mellitus patients. Materials and Methods Data were collected from 3,224 individuals with type 2 diabetes mellitus (male/female: 1,635/1,589; age 61.31 ± 11.45 years), using a retrospective case study design. The association of BMI quintiles and diabetes mellitus vascular complications was assessed using multiple logistic regression models adjusting for age, sex, diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 70 publications
1
36
0
Order By: Relevance
“…A cohort study conducted by Sairenchi et al [ 30 ] in Japan found that a lower BMI in older-adults 60 to 79 years old was associated with a higher risk of developing diabetic complications. Some authors have tried to explain this phenomenon by the fact that lean patients with diabetes have an accelerated loss of pancreatic beta-cells and poorer glycemic control [ 31 ]. However, this pathophysiological paradigm continues to be unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study conducted by Sairenchi et al [ 30 ] in Japan found that a lower BMI in older-adults 60 to 79 years old was associated with a higher risk of developing diabetic complications. Some authors have tried to explain this phenomenon by the fact that lean patients with diabetes have an accelerated loss of pancreatic beta-cells and poorer glycemic control [ 31 ]. However, this pathophysiological paradigm continues to be unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…However, Xu et al hold a diverse view: lower BMI might be a latent risk factor for DPN [22]. Also, a new research from China in which they reported that lower BMI had a dangerous effect on diabetic complications [23]. In the multivariate regression linear analyses, we also found TC was negative with HASYM and FASYM, this is probably because lower TC may indicated that nutrition in patients with DPN was imbalance, which may negatively affected the rehabilitation of DPN [22].…”
Section: Discussionmentioning
confidence: 99%
“…1). The diagnosis of T2DM was diagnosed based on the criteria presented by the American Diabetes Association [10]. Exclusion criteria were type 1 diabetes, gestational diabetes, diabetic ketoacidosis [11], hyperosmolar nonketotic coma, hepatic failure, fasting [12], patients who received SGLT-2 inhibitors, or who lacked data related to the levels of KBs.…”
Section: Study Populationmentioning
confidence: 99%
“…Plasma glucose was measured by glucose oxidase method using the AU2700 analyzer (Olympus Corporation, Tokyo, Japan) and specific reagents. The urinary albumin-tocreatinine ratio (UACR) was calculated as albumin concentration (mg/L) divided by creatinine concentration (g/L) [10]. The eGFR was calculated by the CKD-EPI creatinine equation ( 2009) that can be expressed as a single equation:…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation